2008
DOI: 10.1017/s175569100900704x
|View full text |Cite
|
Sign up to set email alerts
|

Dawsonia Nicholson: linguliform brachiopods, crustacean tail-pieces and a problematicum rather than graptolite ovarian vesicles

Abstract: Though little is known of the graptoloid reproductive mechanism, graptolites with putatively sac-like appendages, supposedly ovarian vesicles, have been known from the Moffat Shales Group, Southern Uplands, Scotland, for over 150 years. Locally, these co-occur with isolated, two-dimensional, discoidal or ovato-triangular fossils. In the 1870s, Nicholson interpreted these isolated fossils as being graptoloid ‘egg-sacs’ detached from their parent and existing as free-swimming bodies. He assigned them to his genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Gürich (1928) recognized the similarity of Dawsonia to Peltocaris. Page et al (2009) discussed the problematical origin and interpretation of the genus Dawsonia.…”
Section: Genera Of Uncertain Relationships and Non-graptolitic Taxamentioning
confidence: 99%
“…Gürich (1928) recognized the similarity of Dawsonia to Peltocaris. Page et al (2009) discussed the problematical origin and interpretation of the genus Dawsonia.…”
Section: Genera Of Uncertain Relationships and Non-graptolitic Taxamentioning
confidence: 99%
“…Comparable structures would be difficult to see in flattened specimens: the delicate layer of cortical tissue that surrounds the site of infestation is much thinner than the fusellar and cortical material that compose the rhabdosome wall, and thin films of cortical fabric are prone to decay and compactional distortion (see discussions of Hallograptus scopulae and the Climacograptus wilsoni vesicle in Page et al . 2009).…”
Section: Interpretation Of the Networkmentioning
confidence: 99%
“…Berdan, 1984;Vannier, Wang & Coen, 2001), contrary to that inferred for the Cardigan arthropods (see Section 7). Similarly, the Cardigan specimens show no resemblance to the elongate and spinose Ordovician bivalved arthropod Caryocaris (see Vannier et al 2003), which though common in graptolitic mudrocks, is of an organophosphatic composition (Churkin, 1966;Page et al 2009).…”
Section: Affinitiesmentioning
confidence: 99%
“…Ruedemann, 1934), arthropods (see Vannier, 2007) and problematica (e.g. Page et al 2009) have been reported. These provide evidence of the existence of a more diverse biota in addition to the graptolites and rare shelly fossils that are typically preserved.…”
Section: Introductionmentioning
confidence: 99%